THE APPLICATION OF STUDENT CENTERED LEARNING THROUGH LESSON STUDY ON QUALITY AND LEARNING RESULTS - Sigit Dwi Saputro (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
This study aims to determine the quality and effectiveness of student learningoutcomes after the student-centered learning approach is applied through lessonstudy. The subjects in this study were students of the Informatics Education StudyProgram at the Faculty of Education, the University of Trunojoyo Madura in thefourth semester in material Elektronik, Analog dan Digital. Data collection techniquesthrough documentation, observation, and tests. The results were: 1) provide leadershipskills, time management, empathy, communication focus, and learning activities, 2)find out the best ways to optimize student learning quality, 3) There were influencelearning outcomes.